Nonsyntenic Genes Drive Highly Dynamic Complementation of Gene Expression in Maize Hybrids. Issue 10 (14th October 2014) - Paschold, Anja; Larson, Nick B.; Marcon, Caroline; Schnable, James C.; Yeh, Cheng-Ting; Lanz, Christa; Nettleton, Dan; Piepho, Hans-Peter; Schnable, Patrick S.; Hochholdinger, Frank
Abstract : This study analyzes how transcriptome diversity between two maize inbred lines affects gene expression patterns in individual root tissues of their F1-hybrid progeny. Tissue-specific variation in single-parent expression (SPE) illustrates the highly dynamic transcriptomic landscape of root tissues. Nonsyntenic genes predominate among SPE genes, indicating their young evolutionary age. Abstract: Maize ( Zea mays ) displays an exceptional level of structural genomic diversity, which is likely unique among higher eukaryotes. In this study, we surveyed how the genetic divergence of two maize inbred lines affects the transcriptomic landscape in four different primary root tissues of their F1-hybrid progeny. An extreme instance of complementation was frequently observed: genes that were expressed in only one parent but in both reciprocal hybrids. This single-parent expression (SPE ) pattern was detected for 2341 genes with up to 1287 SPE patterns per tissue. As a consequence, the number of active genes in hybrids exceeded that of their parents in each tissue by >400. SPE patterns are highly dynamic, as illustrated by their excessive degree of tissue specificity (80%). The biological significance of this type of complementation is underpinned by the observation that a disproportionally high number of SPE genes (75 to 82%) is nonsyntenic, as opposed to all expressed genes (36%). These genes likely evolved after the last whole-genome duplication and are therefore younger than the syntenic genes. In summary, SPE genes shape the remarkable gene expression plasticity between root tissues and complementation in maize hybrids, resulting in a tissue-specific increase of active genes in F1-hybrids compared with their inbred parents.